Fatigue and fracture of medical metallic materials and devices: 3rd volume - Mitchell, Mike; Smith, Stephen William; Woods, Terry; Berg, Brian (Selected technical papers, 2014)
The effects of test speed on fatigue life of nitinol wire in rotary bend / J.D. Weaver, S. Gupta, and T.O. Woods -- The effect of inclusions on fatigue properties for nitinol / M.F. Urbano, A. Coda, S. Beretta, A. Cadelli, and F. Sczerzenie -- Fatigue crack initiation in superelastic nitinol / K.E. Perry and A. Teiche -- In vivo strain estimates for medical implants / K.E. Perry, M.M. Quest, T.J. Johnson, and R. Conta -- Literature discrepancies in biomechanical loading of orthopedic trauma devices intended for lower extremities / A. Whitten and J. Cartner -- Bending fatigue characteristics of orthopedic biomaterials / A. Whitten, J. Cartner, and R. Soileau -- Ti-6AI-4V fatigue strength after shot peening : the role of a corrosive environment / R. Sonntag, J. Reinders, J. Gibmeier, S. Jaeger, and J.P. Kretzer -- Evaluation of the effects of anodization on the fatigue performance of titanium alloy / A. Whitten -- Evaluation of fatigue performance and residual stress of surface modification techniques forTi-6AI-4V medical device applications / S. Terry, J. Rouleau, M. Dace, and M. Pelo -- Fracture toughness and fatigue crack propagation determination of metal matrix composite materials / J. Popp and J. Lessar.
"3rd volume."
"From the Third Symposium on Fatigue and Fracture of Medical Metallic Materials and Devices that was held on November 14, 2012 in Atlanta, Georgia"--Overview page
Includes bibliographical references
Keywords: Congress; Konferenzschrift; Thermomechanische Eigenschaft; Titanlegierung; Nickellegierung; Memory-Legierung; Implantatwerkstoff